Studi kasus ilmu komputer: Efektivitas perancangan model pembelajaran komputasi - Arief Bayu Purnomo; Muhammad Tegar Prakoso; Margaretha Evi (Hexatech: Jurnal Ilmiah Teknik, 2022)
Computational science is a field of science that has attention to the preparation of mathematical models and numerical solution techniques as well as the use of computers to analyze and solve scientific problems (science). Learning from computational theory focuses on answering the main questions about what computing can be done on it and the availability of resources (resources) needed to perform these computations. The learning strategy of Computational Engineering uses a theoretical and practical approach. The learning model used is a brain research learning model. Students must be active during lectures because learning is not only conventional (lecturers explain and students listen), but also with independent assignments, group assignments, presentations, and discussions. The results of the study indicate that this learning model is needed by using a Brain research-based learning model in understanding the basic concepts of Ms. Word and Ms. Excel whose syntax is a) introduction, b) core activities include (i) problem giving phase, (ii) investigation phase, (iii) group discussion phase, (iv) class discussion phase, (v) implementation phase, c) closing.